(3ebOeI CHj GddjKs - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdSeQbfOj GdMfaj ,CHh GddjK,J (B373 (3g` s ((3HcQ CZG Hf dWa Gddg s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd Gdabjg CHh GddjK QVi Gddg Yfg Ke EYde HGH GdUdGI aQjVI bGFeI YQaJ aQjVJgG HGdcJGH hGdSfI hELeGY GdCeI s
(3BNQgG (B:s
(3aEf bjd GdEjeGf LeY Ce JaQjb abd GdEjeGf LeY ai GdbdH hJaQjb Hjf GdCYVGA hGddg CYde HGdUhGH JeJ GdcJGH HYhf Gddg Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B91 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B490s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1795s
Keywords: (3Gdabg GdESdGejs